Yield performance of the cocoa clones of Sca 6 and DRC 15 resistant to vascular-streak dieback - Agung Wahyu Susilo; Surip Mawardi; Sudarsianto Sudarsianto (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2009)
Selection on cocoa resistance to vascular-streak dieback (VSD) has identified some resistant clones for breeding purposes. Of the resistant clones, it was selected Sca 6 and DRC 15 which performing good potential for yield. This paper reports results on testing yield potential of the clones in separate trials. Sca 6 was tested in Kottablater Estate (dry climate in the altitude of ± 25 m asl.) and DRC 15 was tested in Mumbulsari Estate (dry climate in the altitude of ± 45 m asl.) both are in Jember. Trials were arranged in the randomized complete block design with 4 blocks. Evaluation for yield performance was conducted during 6 years of harvest and stability performance was analyzed in regression term using year of harvest as the index. The results indicate the yield potential of the clones was quite similar in the level of 1.4 kg/plant and performing stability during evaluation and good adaptability in the location. The yield potential was lower than the high yielding clones but use of Sca 6 and DRC 15 in heavily infasted VSD area should be considered than using of the susceptible clones. Sca 6 performed low potential on a dry-weight bean in the range of 0.65—0.86 g (class C of quality standard) but better performance could be found in the wet area. DRC 15 performed good potential on a dryweight bean of 1.16 g (class AA of quality standard). Fat content analysis of Sca 6 indicate a better performance of beans which grown up in the wet area (58.2%) than in the dry area (49.6%). It was reported the fat content potential of DRC 15 in the level of 50.4%. Key words: Yield performance, vascular-streak dieback, resistant clone, Theobroma cacao L.